Sistema de faenado avícola y su efecto en la rentabilidad de la empresa Pollo Rey del Cantón la Maná. Periodo 2014-2015. - Montero Ases, Sandy Janeth (2016)
He process comprises the poultry slaughtering system, through which a variety of items, which are derived in the cost of production is marketed well incorporated. This increases or decreases directly affecting profitability. The objective of this research is to determine the impact of poultry slaughtering system on the profitability of the company Pollo Rey Canton La Mana in the period 2014-2015. The largest contribution to the cost of production comes from direct raw material, with a contribution of 95.86% and 95.26% in 2014 and 2015 respectively. This item in the studied period decreased to -6.07%, while the cost of production decreased to -5.48%, the other components of the cost rose to 7.27% on account of direct labor and indirect 11.49% in manufacturing costs. Without reducing costs stated above, increasing the yield it would have been impossible. The guarantee ratio was 2.33 in 2014 and 3.03 in 2015. On the other hand, the stability index of 0.77 in the first year, increasing to 0.92 in 2015, it is concluded that these indices are correct and reflect the good progress of the company. Liquidity ratios comply with suggestions for acceptance, ie close to 2 and about 1. Debt levels are on the order of 0.3, considered as low to meet its obligations, in both years. Financial profitability reached 44.24% in 2014, reaching 43.99% the following year, the same behavior is observed in the economic profitability and capital; It not on the profitability of sales was 2.18% and 2.06% in the period studied. The working capital is quickly recovered, being within acceptable ranges. When comparing these results with the ratios of the commerce sector wholesale and retail provided by the Superintendency of Companies, it is determined that the liquidity ratios, debt and profitability are better for the first, demonstrating the good health of the company Poultry Chicken King.